PEMIKIRAN MUHAMMAD SYAKIR SULA TENTANG SISTEM OPERASIONAL ASURANSI SYARI’AH - Mupidah, Mupidah; Nilawati, Nilawati; Zuraidah, Zuraidah (Muamalah, 2020)
Insurance is a financial services business to raise public funds through the collection of insurance premiums, with the aim of providing protection to members of the community of insurance service users against the possibility of loss due to an uncertain event. The formulation of the problem is the Operational System of Sharia Insurance in Eliminating Gharar, Maisir, and Riba and the Legal Basis used by Muhammad Syakir Sula in Mengelimir Gharar, Maisir and Riba in Sharia Insurance. This research is a library research (Library Research) The source of data obtained from books, tafsir and hadith related to insurance. In the operational system of sharia insurance to eliminate or avoid elements of gharar, maisir can be done with akad akafuli (help and mutual guarantee) by changing the contract and dividing the funds of the participants of both accounts. While usury can be eliminated with a mudarabah agreement (profit sharing) by using the legal basis of Al-Qur'an and Hadith. Keywords: Sharia Insurance, System, Operational